Immunization of cattle with the MSP-1 surface protein complex induces protection against a structurally variant Anaplasma marginale isolate. - Palmer, G H (1989)
The Anaplasma marginale surface protein complex MSP-1 of the Florida isolate is composed of a 105-kilodalton (kDa) polypeptide, which bears a neutralization-sensitive epitope, and a 100-kDa polypeptide. Antigenically similar polypeptides in the Okanogan, Wash. (Washington-O), isolate MSP-1 are 86 and 100 kDa, respectively. Immunization of cattle with Florida isolate MSP-1 induced antibody titers to both MSP-1 polypeptides and protected cattle against homologous and heterologous challenge.